The behavior of reinforced blockwork masonry columns under axial compression - Özsoy, Ayşe Elif. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2003., 2003)
Reinforced masonry columns are common structural elements which are used for supporting compressive vertical loads and providing lateral support to masonry walls. Reinforcement increases the column resistance to axial and flexural loading as long as it is confined by lateral ties. The reinforcing cage also confines the concrete core of the masonry columns and increases the ductility of the member. Reinforced masonry columns have the advantage of eliminating the need for formwork by using hollow block units. An experimental and analytical study was performed on the ultimate strength and failure mechanism of reinforced masonry columns under axial loading. A total of six columns were constructed as nine course high using 190x190~390m m two core hollow concrete block units. The effect of using variable compressive strength of infill concrete on the ultimate strength was also investigated. In addition to the experimental study, threedimensional nonlinear finite element modelling of the columns was developed in order to investigate the nonlinear behavior of reinforced masonry columns under axial loading, analytically.
Keywords: Reinforced concrete.; Columns, Concrete.; Reinforced concrete construction.